2019
DOI: 10.31234/osf.io/9a68c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do voices carry valid information about a speaker's personality?

Abstract: Research on links between peoples’ personality traits and their voices has primarily focused on other peoples’ personality judgments about a target person based on a target person’s vocal characteristics, particularly voice pitch. However, it remains unclear whether individual differences in voices are linked to actual individual differences in personality traits, and thus whether vocal characteristics are indeed valid cues to personality. Here, we investigate how the personality traits of the Five Factor Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our results show a negative correlation between mean fundamental frequency and sociosexual behavior -as measured by the behavior facet of the Revised Sociosexual Orientation Inventory (Penke and Asendorpf, 2008) -in males (r 100 = −0.27, p = 0.023; 95%CI = [−0.45, −0.07]) but not in females (r 147 = −0.17 , p = 0.103, 95%CI = [−0.32, −0.00]); in other words, our findings show a trend where men with lower-pitched voices exhibit a more unrestricted sexual behavior. This association is in line with previous studies which have shown that male-speech lower F0 is related to higher scores on the SOI-R scale (Valentova et al, 2019;Stern et al, 2021) and that males with lower-pitched voices have higher reproductive success and more children born to them (Apicella et al, 2007). While Stern et al (2021) did find an association between voice pitch and sociosexuality in women, neither the studies by Apicella et al (2007) and Valentova et al (2019) nor the present study found an association between female F0 and sociosexuality.…”
Section: Discussionsupporting
confidence: 91%
“…Our results show a negative correlation between mean fundamental frequency and sociosexual behavior -as measured by the behavior facet of the Revised Sociosexual Orientation Inventory (Penke and Asendorpf, 2008) -in males (r 100 = −0.27, p = 0.023; 95%CI = [−0.45, −0.07]) but not in females (r 147 = −0.17 , p = 0.103, 95%CI = [−0.32, −0.00]); in other words, our findings show a trend where men with lower-pitched voices exhibit a more unrestricted sexual behavior. This association is in line with previous studies which have shown that male-speech lower F0 is related to higher scores on the SOI-R scale (Valentova et al, 2019;Stern et al, 2021) and that males with lower-pitched voices have higher reproductive success and more children born to them (Apicella et al, 2007). While Stern et al (2021) did find an association between voice pitch and sociosexuality in women, neither the studies by Apicella et al (2007) and Valentova et al (2019) nor the present study found an association between female F0 and sociosexuality.…”
Section: Discussionsupporting
confidence: 91%
“…3D facial FA measurement. Participants' faces were 3D-scanned twice for men and overall twelve times for women (thrice for each of 2 sessions during the luteal phase and sessions during the fertile phase of their ovulatory cycles, of which the scans from the first luteal sessions were used, see Jünger et al, 2018 andStern et al, 2019 for details) using a 3dMD face scanner. For each participant one scan was chosen with the most neutral facial expression and standardized head position, while some participants (males: n = 28, females: n = 4) had to be excluded due to poor scan quality or interfering facial hair for the males.…”
Section: Methodsmentioning
confidence: 99%
“…The final sentence was used for voice ratings (mean length of the voice stimuli = 7.36 secs, SD = 0.91 secs). Since women's voice were recorded four times (twice per fertility status, see Jünger et al, 2018 andStern et al, 2019), the recordings concurrent with the face scans from the first infertile session were used. After excluding five recordings for men due to technical issues and participants not wanting their recordings to be used further, the final stimulus sets comprised 160 recordings for men and 157 for women.…”
Section: Methodsmentioning
confidence: 99%
“…Participants' faces were 3D-scanned twice for men and overall twelve times for women (three times for each of two sessions during the luteal phase and two sessions during the fertile phase of their ovulatory cycles, of which the scans from the first luteal sessions were used, see Jünger et al, 2018 andStern et al, 2019 for details) using a 3dMD face scanner. For each participant one scan was chosen with the most neutral facial expression and standardized head position, while some participants (males: n = 28, females: n = 4) had to be excluded owing to poor scan quality or interfering facial hair for the males.…”
Section: D Facial Fa Measurementmentioning
confidence: 99%
“…The final sentence was used for voice ratings (mean length of the voice stimuli = 7.36 s, SD = 0.91 s). Since women's voices were recorded four times (twice per fertility status, see Jünger et al, 2018 andStern et al, 2019), the recordings concurrent with the face scans from the first infertile session were used. After excluding five recordings for men owing to technical issues and participants not wanting their recordings to be used further, the final stimulus sets comprised 160 recordings for men and 157 for women.…”
Section: Voice Recordingsmentioning
confidence: 99%